Epiphytic bryophytes of urban agroforests in Ibadan, southwest Nigeria. (2nd October 2019) - Ezukanma, Izuchukwu O.; Tessler, Michael; Salaam, Adebayo M.; Chukwuka, Kanayo S.; Ogunniran, Ademola J.
ABSTRACT: Introduction. Agroforests are often surrogate habitats for threatened bryophytes and other organisms. This is important in urban settings where natural forests are often absent. Unfortunately, the benefits of urban agroforests for biodiversity are rarely studied. Methods. To better understand the bryophyte diversity of agroforests, we studied corticolous bryophytes (≤ 2 m) on 30 trees each in Citrus L. and Mangifera L. plantations in Nigeria. Key results. Nineteen species were recorded: 13 leafy liverworts and six mosses. Twelve species were recorded per plantation. Five species were shared between the two agroforests, indicating that a diversity of agroforests is ideal for preserving bryophyte diversity. Bryophyte abundance in the agroforests was similar, but the species were more evenly distributed and the diversity was higher in the mango agroforest. The frequent pruning of the crown (a standard horticultural practice) in the mango agroforest may relate to these differences. Calymperes palisotii was the most abundant species recorded in the study and was particularly abundant in the Citrus plantation. Generally, corticolous species were absent from the tree base, but occur at a higher mean height on mango (1.39 m) than on Citrus (1.11 m). This may be due to differences in species, or management practices. The height range for epiphytic bryophytes is slightly broader (0.48–1.80 m) in the Citrus plantation than in the mango plantation (1.17–1.60 m). However, the height of occurrence of bryophyte species in Citrus was generally lower, except for the moss Rhacopilopsis trinitensis, which has the maximum mean height on the trunk.